Effects of Dexmedetomidine or Propofol on Postoperative Oxygenation Index During Invasive Ventilation in Patients After off-Pump Coronary Artery Bypass Grafting: a Single-Center Retrospective Study - Li F; Ma L; Yan S; Liu D (International Journal of General Medicine)
Fang Li,1 Luwei Ma,1 Suhua Yan,2 Dongyi Liu3 1Department of Cardiac Surgery, Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 2Department of Cardiovascular Medicine, Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 3Department of Anaesthesiology, The Second Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of ChinaCorrespondence: Luwei Ma, Department of Cardiac Surgery, Provincial Hospital Affiliated to Shandong First Medical University, 324 Jingwu Weiqi Road, Jinan, Shandong, 250021, People’s Republic of China, Tel +0086- 151 6515 6952, Email lwma535@126.comPurpose: This study aimed to compare the effects of dexmedetomidine (DEX) and propofol on patients undergoing invasive ventilation after off-pump coronary artery bypass grafting (OPCABG) with regard to oxygenation index (OI) (PaO2/FiO2), hemodynamic changes, extubation time, and adverse reactions.Patients and Methods: This single-center retrospective study included 195 patients admitted to the cardiovascular surgery intensive care unit (CVICU) after OPCABG between January 2022 and June 2024. According to the postoperative invasive mechanical ventilation for sedation with only DEX or propofol, the patients were classified into groups D and P. The primary outcome was oxygenation index (OI) before and after extubation. The secondary outcomes included mean arterial pressure (MAP) and heart rate (HR) before and after extubation, extubation time, and adverse reactions after surgery.Results: DEX was significantly associated with an increased likelihood of OI before and after extubation composed to propofol (P < 0.05). MAP and HR after extubation were significantly higher than before extubation in Group P (P < 0.05). However, there were no significant differences between before and after extubation in Group D (P < 0.05). Furthermore, MAP and HR were significantly lower in Group D than in Group P before and after extubation (P < 0.05). In addition, the extubation time was significantly shorter in Group D in comparison of propofol (P < 0.05). Additionally, the incidence of delirium and severe cough at extubation after surgery was significantly lower in Group D than in Group P (P < 0.05).Conclusion: DEX may support satisfactory OI, good hemodynamic stability, rapid extubation time, and a lower incidence of adverse reactions for sedation of mechanically ventilated patients following OPCABG surgery compared to propofol, although the difference with OI did not reach the MCID.Keywords: dexmedetomidine, propofol, oxygenation index, invasive ventilation, off-pump coronary artery bypass grafting